Skiing and snowboarding head injury: A retrospective centre-based study and implications for helmet test standards. (March 2020) - Stuart, C.A.; Brubacher, J.R.; Yau, L.; Yip, R.; Cripton, P.A.
Abstract: Background: Head injury occurs in up to 47% of skiing or snowboarding injuries and is the predominant cause of death in these sports. In most existing literature reporting injury type and prevalence, head injury mechanisms are underreported. Thus, protective equipment design relies on safety evaluation test protocols that are likely oversimplified. This study aims to characterize severity and mechanism of head injuries suffered while skiing and snowboarding in a form appropriate to supplement existing helmet evaluation methods. Methods: A 6-year, multicentre, retrospective clinical record review used emergency databases from two major trauma centres and Coroner's reports to identify relevant cases which indicated head impact. Records were investigated to understand the relationships between helmet use, injury type and severity, and injury mechanism. Descriptive statistics and odds ratios aided interpretation of the data. Findings: The snow sport head injury database included 766 cases. "Simple fall", "jump impact" and "impact with object" were the most common injury mechanisms while concussion was observed to be the most common injury type. Compared to "edge catch", moderate or serious head injury was more common for "fall from height" (OR = 4.69; 95% CI = 1.44–16.23; P = 0.05), "jump impact" (OR = 3.18; 95% CI = 1.48–7.26; P = 0.01) and "impact with object" (OR = 2.44; 95% CI = 1.14–5.56; P = 0.05). Occipital head impact was associated with increased odds of concussion (OR = 7.46; 95% CI = 4.55–12.56; P = 0.001). Interpretation: Snow sport head injury mechanisms are complex and cannot be represented through a single impact scenario. By relating clinical data to injury mechanism, improved evaluation methods for protective measures and ultimately better protection can be achieved. Highlights: Snow sport head injury cannot be represented by a single mechanism as practiced in safety standards. Concussion is the most prevalent injury type of head injury for skiing and snowboarding. A high prevalence of low energy injuries in contrast to high energy injuries suggests a need for better low energy protection. Low and high velocity tests, as well as oblique tests, are necessary to best evaluate head protection. These findings may aid in development of revised, more representative helmet certification testing protocols.